The Use of Accountability Reports and the Accountability Forum: Evidence from an Indonesian Local Government - Muhammad Hudaya; Ciorstan Smark; Ted Watts; Parulian Silaen (Australasian Accounting, Business and Finance Journal, 2015)
This article explores the changing accountability role that Indonesian local government reporting has played by exploring a Local Government Under Study’s (LGUS) accountability report process. The study uses an interpretive (social constructionist) methodology. A case study method (including historical records and interviews, as well as direct observations) is used through an institutional theory lens to interpret local reporting behaviour. Local government currently submits accountability reports to three parties: the central government, the local parliament and the public. However, while the public now receives a report, it contains only a summary of the report submitted to the central government and is often not made available in a timely manner. The authors recommend that a full report (in similar format and detail to that made available to Central Government) be made available to the public. The accountability forum is currently largely ceremonial and symbolic. In order to better meet the requirements of accountability, the authors recommend that this forum allow for questions about the Local Governments’ activities to be asked and responded to in a public forum. As with any case study, themes reflected in this study are not necessarily generalizable.
Keywords: Accountability; Indonesia; Local Government; Reporting